Development and validation of HPLC method for the quantification of clotrimazole in a gelatin film formulation - Surekha Kalshetti; K. P. Rao (SpringerOpen, 2021)
Abstract Background Clotrimazole is used to treat topical vaginal yeast infections. Vaginal gelatin film formulations of clotrimazole were prepared, and the present study aims to develop an HPLC method for quantifying clotrimazole in the film formulation. Results The chromatographic separation of components was achieved on a Phenomenex Luna C18(2) (150 × 4.6 mm, 5 μm) stationary phase with Phenomenex Security Guard Cartridge C18 (4 × 3 mm) using acetonitrile and water (70:30% v/v) as mobile phase. The flow rate was 1.0 ml/min and the absorbance was monitored at 210 nm. Clotrimazole was eluted at 5.6 min. The procedures and capabilities of the method were evaluated against the criteria for system suitability, specificity, linearity, precision, accuracy, and robustness as defined by the ICH guidelines. The method showed good linearity (R 2 = 0.999) in the range of 10-50 μg/ml and an average recovery of 101.05%. Conclusion The method could be applied for the quantification of clotrimazole in the gelatin film formulation.